Prevalence and Factors Associated with Psychosocial Distress Among Adolescents in Beninese Schools in 2016 - Agbohoui Houinato, Olga; KLIKPO, Tchédié Etdéchié Elvyre; HOUNKPATIN, BENJAMIN IGNACE B.; KPOZEHOUEN, ALPHONSE; Gbédji, Kévin Yann; Yoro Zohoun, Inès; Guédou, Fernand; HOUINATO, DISMAND STÉPHANE; PERRIN, RENÉ-XAVIER (My University, 2019)
Context: Adolescence is the period during which a person experiences significant physical, biological and emotional changes. The lack of attention to mental well- being of adolescents may have adverse consequences on their mental health. The objective of this study was to estimate the prevalence of psychological distress in schooled adolescents and the factors associated with it. Methods: This was a cross-sectional study conducted in 2016 and involving 3,841 adolescents of 10 to 19 years from 40 secondary schools in Benin. Participants were selected using a 2-level random sampling technique. Data were collected through a self-administered questionnaire and were analyzed using Epi Info and Stata softwares. Associated factors were investigated by a logistic regression. Results: Mean age was 16.54 ± 0.04 years and sex ratio was 1.16. The prevalence of psychosocial distress was 10.8% CI 95% 1, 4 2 : 9.44–12.15). Multivariate analysis showed a significant association between bullying, friendships, the class attended, the place of residence and the person with whom the adolescent lives. Teenagers who had been bullied were almost twice as likely to develop psychosocial distress. Having a close friend was a protective factor from psychosocial distress. Being in examination years (9 th grade or final year of high school) increased by 4 times the risk of developing psychosocial distress. Conclusion: Psychosocial distress, previously mostly observed in developed countries, is now also reaching emerging countries. The implementation of urgent actions for the prevention of psychosocial distress is imposed on decision-makers.
Keywords: Prevalence; Psychosocial Distress; Adolescent; School Environment; Benin